Optimal taxation and constrained inefficiency in an infinite-horizon economy with incomplete markets - Piero Gottardi; Atsushi Kajii; Tomoyuki Nakajima (Center for Economic Studies and ifo Institute (CESifo), 2011)
We study the dynamic Ramsey problem of finding optimal public debt and linear taxes on capital and labor income within a tractable infinite horizon model with incomplete markets. With zero public expenditure and debt, it is optimal to tax the risky labor income and subsidize capital, while a positive amount of public debt is welfare improving. A steady state optimality condition is derived which implies that the tax on capital is positive, when savings are sufficiently inelastic to returns. A calibration of our model to the US economy indicates positive optimal taxes and a small but positive optimal debt level.
Keywords: D52; D60; D90; E20; E62; H21; O40; 330; incomplete markets; Ramsey equilibrium; optimal taxation; optimal public debt; constrained inefficiency; Optimale Besteuerung; Öffentliche Schulden; Optimales Wachstum; Unvollkommener Markt; Theorie